The psychology of genocide, massacres, and extreme violence: why "normal" people come to commit atrocities - Dutton, Donald G. (Praeger Security International, 2007)
Historical background of massacre : the crusades and the concept of "holy war" to rationalize violence -- 20th century genocides : focused extinction of a people versus extreme aggression as an instrument of control -- Genocide : Armenia, the Holomodor, Cambodia , Rwanda, the killing fields Bosnia -- The Holocaust -- Massacres : the rape of Nanking , My Lai, El Mozote, and Sand Creek -- Lynchings -- Prison riots -- Societal transitions -- Individual transitions to evil -- Forensics of war -- Individual differences in susceptibility to transition